Толерантность как психолого-социальный феномен - Швачко, Е. (Социология: теория, методы, маркетинг, 2001)
The tolerance term has been analyzed in the context of general humanity and history. There are presented a series of findings related to the nature of tolerance and social grounds of its formation in the young people’s consciousness. The psychological mechanism of the tolerance development and implementation was studied in small test groups of young people.